A Deficiency of the Psychiatric Risk Gene DLG2/PSD-93 Causes Excitatory Synaptic Deficits in the Dorsolateral Striatum - Yoo, Taesun; Joshi, Shambhu; Prajapati, Sanjaya; Cho, Yi Sul; Kim, Jinkyeong; Park, Pil-Hoon; Bae, Yong Chul; Kim, Eunjoon; Kim, Soo Young (Frontiers in Molecular Neuroscience, 2022)
Genetic variations resulting in the loss of function of the discs large homologs (DLG2)/postsynaptic density protein-93 (PSD-93) gene have been implicated in the increased risk for schizophrenia, intellectual disability, and autism spectrum disorders (ASDs). Previously, we have reported that mice lacking exon 14 of the Dlg2 gene (Dlg2–/– mice) display autistic-like behaviors, including social deficits and increased repetitive behaviors, as well as suppressed spontaneous excitatory postsynaptic currents in the striatum. However, the neural substrate underpinning such aberrant synaptic network activity remains unclear. Here, we found that the corticostriatal synaptic transmission was significantly impaired in Dlg2–/– mice, which did not seem attributed to defects in presynaptic releases of cortical neurons, but to the reduced number of functional synapses in the striatum, as manifested in the suppressed frequency of miniature excitatory postsynaptic currents in spiny projection neurons (SPNs). Using transmission electron microscopy, we found that both the density of postsynaptic densities and the fraction of perforated synapses were significantly decreased in the Dlg2–/– dorsolateral striatum. The density of dendritic spines was significantly reduced in striatal SPNs, but notably, not in the cortical pyramidal neurons of Dlg2–/– mice. Furthermore, a DLG2/PSD-93 deficiency resulted in the compensatory increases of DLG4/PSD-95 and decreases in the expression of TrkA in the striatum, but not particularly in the cortex. These results suggest that striatal dysfunction might play a role in the pathology of psychiatric disorders that are associated with a disruption of the Dlg2 gene.